PLIKASI TEKNOLOGI KNOCK DOWN UNTUK PEMBANGUNAN RUMAH DAN SEKOLAH TERBUKA KORBAN BENCANA TSUNAMI DI ACEH DAN SUMATERA UTARA - Sugestiyadi, Bambang (Universitas Negeri Yogyakarta, 2005)
In the framework of realization of Tri Darma Perguruan Tinggi program, Technique Faculty of Yogyakarta State University (YSU) contributes idea for Tsunami disaster victims in Aceh and North Sumatra that was happened on 26th December 2004. The contribution of the Technique Faculty of Yogyakarta State University (YSU) for Tsunami disaster in Aceh and North Sumatra is given in the form of a Planning Concept of Housing and Open Schools.The planning for Houses and opens Schools for Tsunami disastervictims in Aceh and North Sumatra is consideres with many aspects, i.e. : (1) Functional aspect, (2) Social culture aspect, (3) Construction aspect (in relation with nature condition and disaster), (4) Technical aspect, (5) Economical aspect, and (6) Field implementation aspect.The result of the planning for Housing and Open Schools is suitablewith geographical condition in Aceh and its emergency condition that is happening there, and North Sumatra after Tsunami are as follows: (a) In the form of house on stilts, (b) 'Knock Down' construction system, (c) Using local wood, and (d) House construction that can put up with earthquake.Key words: Housing and Open Schools, After Tsunami